The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3991/ijim.v16i02.27295
|View full text |Cite
|
Sign up to set email alerts
|

The Elements of Computational Thinking in Learning Geometry by Using Augmented Reality Application

Abstract: Augmented Reality (AR) technology has now become a growing trend within the education field. It has the capability to combine both digital and reality world that subsequently leads to the emergence of new possibilities in im-proving the quality of teaching and learning activities. The objective of this research is mainly to analyse the Computational thinking elements in solving Geometry topic after the intervention of AR application. Qualitative data analysis was employed as the research methodology of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…These findings are supported by two studies, namely Lai and Ruhizan (2022) and Wilson and Narasuman (2020), which found that teachers' knowledge and design thinking skills were low and that there was lack of technology usage. Therefore, Hanid et al (2022) argued that the use of currently available technology can help teachers' problem-solving skills in teaching and learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are supported by two studies, namely Lai and Ruhizan (2022) and Wilson and Narasuman (2020), which found that teachers' knowledge and design thinking skills were low and that there was lack of technology usage. Therefore, Hanid et al (2022) argued that the use of currently available technology can help teachers' problem-solving skills in teaching and learning.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to Song (2019), by integrating technology into constructive student activities, they would be able to explore learning independently. In fact, research carried out by Abdul Hanid et al (2022) has proven that technology is not only a teaching aid but can also be integrated to solve problems in teaching and learning. The resulting behaviour makes it easier for teachers to measure how students transfer knowledge and skills to solve problems (Reynders et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dalam jenjang Sekolah Dasar (SD) salah satu materi yang dipelajarinya yaitu geometri, dimana geometri ini mempelajari tentang bentuk, garis dan ruang yang dapat ditempati (Hanid, 2022;Hershkowitz, 2020;Indasari & Ratna, 2019). Pembelajaran matematika pada geometri ini mempelajari tentang bidang, bangun datar, bangun ruang, kesebangunan, semi putar, semi lipat, garis, sudut dan kongruens (Nafi'ah & Indrawati, 2019).…”
Section: Pendahuluanunclassified